2014
DOI: 10.1063/1.4897416
|View full text |Cite
|
Sign up to set email alerts
|

Frustration phenomena in Josephson point contacts between single-band and three-band superconductors

Abstract: Within the formalism of Usadel equations the Josephson effect in dirty point contacts between single-band and three-band superconductors is investigated. The general expression for the Josephson current, which is valid for arbitrary temperatures, is obtained. We calculate current-phase relations for very low temperature and in the vicinity of the critical temperature. For three-band superconductors with broken time-reversal symmetry (BTRS) point contacts undergo frustration phenomena with different current-pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The opposite case, namely, the diffusion limit of a microcontact formed by a single-band and three-band superconductor with time-reversal symmetry breaking, has been considered in Ref. 113. As in the KO-1 theory, 102 the pointcontact geometry allows to reduce the problem to onedimensional Usadel equations, generalized only to three energy gaps, in which all terms but the gradient are discarded.…”
Section: Scs Microcontactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite case, namely, the diffusion limit of a microcontact formed by a single-band and three-band superconductor with time-reversal symmetry breaking, has been considered in Ref. 113. As in the KO-1 theory, 102 the pointcontact geometry allows to reduce the problem to onedimensional Usadel equations, generalized only to three energy gaps, in which all terms but the gradient are discarded.…”
Section: Scs Microcontactsmentioning
confidence: 99%
“…Despite the presence of two possible current-phase relations in Josephson junctions, 113 the i c ¼ i c (U e /U 0 ) dependence is the same for both ground states [ Fig. 30(a)].…”
Section: Quantum Interferometers Based On Multiband Superconductorsmentioning
confidence: 99%
“…Following the notations introduced earlier about phases of contacting superconductors (see Ref. 17) we denote the phase difference on the contact between the first order parameter of a threeband superconductor and the order parameter of the single-band superconducting part of the SQUID loop as i χ , where 1, 2 i = are index of the contact. The single-valuedness of the phase differences around the loop, which are thicker than the London penetration depth for the singleand three-band superconductors, requires…”
Section: Main Equationsmentioning
confidence: 99%
“…Motivated by these unresolved challenges we address the problem of the dynamics of the dc SQUID with Josephson point contacts between a conventional s-wave and an isotropic dirty three-band s-wave superconductors. Using earlier obtained results on the Josephson effect in such superconducting systems [17], we investigate dependencies of the total flux in the dc SQUID from the externally applied flux (S states) and the magnetic field dependence of the critical current. We show, what new kind of features and effects for the characteristics of the dc SQUID we can expect due to the multi-band structure of the order parameter with possible manifestation of the BTRS state.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated the Josephson effect [32] and the behavior of a dc SQUID with Josephson point contacts between an s-wave superconductor and a three-band isotropic superconductor in the dirty limit [30] We have revealed the unusual dependence of the critical current on the external magnetic flux and demonstrated the possibility of appearance of multihysteresis loops in the dependence of the total flux on the external magnetic flux. It was found that all these features of Josephson systems are associated with BTRS.…”
Section: Introductionmentioning
confidence: 99%